Meningiomatosis Restricted to the Left Cerebral Hemisphere Presenting with Frontal Lobe Seizure: A Short Communication - Biniyam A. Ayele; Hilina Dagnachew; Meskerem Nimani; Jarsso Tadesse Hirbu (Sudan Journal of Medical Sciences, 2024)
Seizures are a common clinical feature of benign intracranial brain tumors such as meningioma. Although seizures are cortical phenomena that typically originate from lesions affecting cortical neurons, meningiomas, which arise from the meningeal lining, can still induce seizures due to their proximity to the cerebral cortex. However, the relationship between multiple meningiomas and frontal lobe seizures remains underexplored. We present the case of a 42-year-old woman without neurofibromatosis who experienced global headaches and nocturnal motor seizure involving the right hemi body, associated with loss of consciousness. The motor fits frequently occur at night. Brain magnetic resonance image (MRI) and electroencephalograph (EEG) show multiple meningioma and left frontal epileptogenic focus, respectively. The patient was managed conservatively with anticonvulsant.